2020
DOI: 10.1002/etc.4642
|View full text |Cite
|
Sign up to set email alerts
|

Strong Adsorption of Dieldrin by Parent and Processed Montmorillonite Clays

Abstract: Widespread use of pesticides has resulted in the accumulation of pesticide residues in the environment due to their persistence and stability. To reduce potential exposures, we have developed broad‐acting clay‐based sorbents that can be included in the diet as enterosorbents to reduce the bioavailability and toxicity of chemicals. In the present study, parent and acid‐processed calcium montmorillonite clays (CM and APM, respectively) were used to determine their potential as sorbents of the organochlorine inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Among them, the pollution of groundwater by pesticides was particularly affected according to report by researchers (Kumari & John, 2019;Shokoohi et al, 2019;Xiao et al, 2019). The principal factor affecting the pollution of groundwater by pesticides was the migration and persistence of pesticides in the soil (Hearon et al, 2019;López-Ruiz et al, 2019;Y. C. Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the pollution of groundwater by pesticides was particularly affected according to report by researchers (Kumari & John, 2019;Shokoohi et al, 2019;Xiao et al, 2019). The principal factor affecting the pollution of groundwater by pesticides was the migration and persistence of pesticides in the soil (Hearon et al, 2019;López-Ruiz et al, 2019;Y. C. Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The migration of pesticides in the soil was closely related to the water solubility and adsorption characteristics of pesticides and other factors. It was a principal index to assess the ecological environment of pesticides (Duchowicz, 2020;Hearon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption, desorption and leaching potential of glyphosate and aminomethylphosphonic acid [ 52 ], adsorption of dieldrin by parent and processed montmorillonite clays [ 53 ] and other pesticides were studied including the biodegradation of pesticides by soil bacteria [ 54 , 55 , 56 ].…”
Section: Herbicide-absorption and Translocation In The Soil-plants Systemsmentioning
confidence: 99%
“…Materials such as activated carbon (AC) and clay-based sorbents have been used to bind various contaminants in the environment to reduce their bioavailability. Studies from our laboratory have shown that montmorillonite-based clays are highly effective sorbents for mycotoxins, pesticides, PAHs, and PCBs (Hearon et al, 2020;Phillips et al, 2019;Wang et al, 2019a, Wang et al, 2019bWang et al, 2020). We have recently shown that calcium montmorillonite (CM) clay can tightly bind PMG to active surfaces based on adsorption studies and computational modeling (Wang et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%